Using gene fund of wild relatives for common wheat improvement (International Journal of Biology and Chemistry, 2014)
The article describes the research results, the method of distant hybridization can provide to get new genotypes with new parameters, high-yielding, immune, with a high content of protein in the grain and adapted to environmental conditions.